INTEGRATING FISH INTO RICE FARMING AS AN ECONOMIC SUBSTITUTE TO CHEMICAL PESTICIDES - Mercy Muthoni Wambugu; Dr. Ezekiel Ndunda; Dr. Gladys Gathuru, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
In an effort to eradicate pests and significantly increase food production for sustainable agriculture, rice farmers in Kenya have bowed to intensive and indiscriminate utilization of agrochemicals, particularly the chemical pesticides. Consequently, extensive use of pesticides in rice farming has become an integral part of production of the crop. Increasing empirical evidence suggests that chemical pesticides have intrinsic environmental risks during their use, storage and disposal, posing serious ecological and health concerns. However, most empirical studies on mitigation measure have proposed utilization of integrated pest management methods to control use of pesticides and minimize the effects of these pesticides as others examined the viability of integrating fish into rice farming and the rest revealed a sustainable rice agro-ecosystem. Related studies conducted locally have scantly addressed the rice-fish integrated farming approach as an economic alternative mechanism to chemical pesticides, denying Kenyan rice farmers at Mwea irrigation scheme important information for propagating a healthy environment. This study sought to lock this gap by assessing the economic viability of integration of fish into rice farming as substitute to chemical pesticides at farms in Mwea Irrigation Scheme. The present study adopted experimental design using completely randomized block design undertaken in the rice field of Mwea irrigation scheme. The experiment comprised of three separate treatments, each replicated three times with the; first treatment having rice, stocked with fish and fertilized with regular urea fertilization; second treatment had rice, stocked with fish, partial fertilization and supplementary feeding, and the third treatment was kept as control (rice without fish). Pishori variety of rice plants was be transplanted in the paddy field and after 14 days of transplantation of rice plants, fingerlings of Nile Tilapia were released in on two plots. Rearing was done at two levels: fish present (rice-fish culture) and fish absent (rice-monoculture). Data on rice and fish growth was collected at intervals after three months of the project initiation. The study concludes that integrating Nile tilapia fish into rice farming increases rice yields and increase fish produce. Accordingly, there is increased net returns from rice and fish, reduction of chemical pesticides utilization (eliminate the use pesticides), increase of the farmers’ income, diversified productivity of the soil, soil protection, increased nutrients uptake and biological control of pests.